2020
DOI: 10.3390/ijerph17072524
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Helicobacter pylori Infection and Irritable Bowel Syndrome: A Meta-Analysis

Abstract: The association of Helicobacter pylori (H. pylori) infection with functional dyspepsia has been well studied. However, the data on the relationship between H. pylori infection and irritable bowel syndrome (IBS) are conflicting. This study aims to elucidate the association between H. pylori infection and IBS. PubMed, Cochrane Library, CINAHL and SCOPUS databases were searched to identify eligible English articles published up to December 2019. Cross-sectional studies, case-control studies and cohort studies rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 46 publications
1
6
0
1
Order By: Relevance
“…As Clostridium difficile releases toxins that are detrimental to the enteric glial cells, neurons, colonocytes, and enterocytes, it disrupts the gut homeostasis [ 28 ]. Helicobacter pylori is a Gram-negative bacterium normally found in the mucous epithelium of the gut [ 30 ]. This pathogenic microbial was recently reported to cause systemic inflammation, visceral hypersensitivity at the upper GI tract, and increased gut permeability [ 28 , 30 ].…”
Section: Irritable Bowel Syndrome and Gut Dysbiosismentioning
confidence: 99%
See 1 more Smart Citation
“…As Clostridium difficile releases toxins that are detrimental to the enteric glial cells, neurons, colonocytes, and enterocytes, it disrupts the gut homeostasis [ 28 ]. Helicobacter pylori is a Gram-negative bacterium normally found in the mucous epithelium of the gut [ 30 ]. This pathogenic microbial was recently reported to cause systemic inflammation, visceral hypersensitivity at the upper GI tract, and increased gut permeability [ 28 , 30 ].…”
Section: Irritable Bowel Syndrome and Gut Dysbiosismentioning
confidence: 99%
“…Helicobacter pylori is a Gram-negative bacterium normally found in the mucous epithelium of the gut [ 30 ]. This pathogenic microbial was recently reported to cause systemic inflammation, visceral hypersensitivity at the upper GI tract, and increased gut permeability [ 28 , 30 ].…”
Section: Irritable Bowel Syndrome and Gut Dysbiosismentioning
confidence: 99%
“…In the present study, neither FGIDs nor gastric HSV-1 infection was associated with histologically identified gastritis. The literature contains conflicting reports on the association of H. pylori infection with FGIDs [58][59][60][61][62][63][69][70][71]. In our study population, H. pylori was more prevalent in control patients than in case patients and was not associated with FGIDs.…”
Section: Discussionmentioning
confidence: 75%
“…Ng QX et al suggested in one meta-analysis that IBS sufferers may have an increased probability of H. pylori infection, but this was not significant statistically 12 . H. pylori infection has not been significantly linked to IBS in a recent meta-analysis 8 .…”
Section: Introductionmentioning
confidence: 90%